Nonlinear ptychographic coherent diffractive imaging - Odstrcil, M.; Baksh, P.; Gawith, C.; Vrcelj, Ranko; Frey, J. G.; Brocklesby, W. S. (Optical Society of America, 2016)
Ptychographic Coherent diffractive imaging (PCDI) is a significant advance in imaging allowing the measurement of the full electric field at a sample without use of any imaging optics. So far it has been confined solely to imaging of linear optical responses. In this paper we show that because of the coherence-preserving nature of nonlinear optical interactions, PCDI can be generalised to nonlinear optical imaging. We demonstrate second harmonic generation PCDI, directly revealing phase information about the nonlinear coefficients, and showing the general applicability of PCDI to nonlinear interactions.
Keywords: Imaging systems; Coherence imaging; Nonlinear microscopy